Methodological process to plan and implement an educational Campaign to increase bean consumption. - Rodríguez, Ligia (2004)
This article describes planning of an educational Campaign toincrease bean consumption, and the activities carried outduring its implementation. At the same time, it highlights thecontributions of an initial assessment and the result of thefinal evaluation. Finally, the article summarizes the “lessonslearned” during implementation of these two phases, andprovides considerations about their importance andapplicability. Other “lessons learned” throughout the processare also included.